Trabalho, ruído e saúde dos profissionais de uma lavanderia hospitalar - Fontoura, Francisca Pinheiro (2011)
Hospital laundries as workplaces are a serious problem regarding working environment conditions. Such conditions contain risks that compromise the worker’s health and safety and, as a consequence, enable the occurrence of accidents and the development of occupational diseases. This study’s main goal was to identify the general working conditions and the noise impact on workers' health in a hospital laundry. Method: the research was carried out at the laundry of a university hospital located in the city of Curitiba, state of Paraná, Brazil, through a quantitative and qualitative approach, which was developed in four stages. The analysis of the PPRA (Environmental Risk Prevention Program) and PCMSO (Medical Control and Occupational Health Program) was conducted at the first stage. The data collection was carried out at the second stage, using a questionnaire from Ibañez, Schneider, Seligman (2001) which is based on the medical history of the workers exposed to noise. The audiometric data obtained from the workers through tonal threshold audiometry were collected at the third stage, and at the fourth stage the data were collected through focal group technique. Results: Ninety-five laundry workers took part of the study, their ages varied from 20 to 59 (an average of 38.26), of which 57.89% were female and 42.11% were male. Results: The sound pressure level found at the laundry varied between 75.6 dB(A) and 99.0 dB(A). The analysis of the auditory evaluations showed that 37.89% of the workers presented altered audiogram results, 18.94% had sensoneurial auditory loss with characteristics that suggest NIHL (Noise-Induced Hearing Loss). At the focal group, several categories were elected for analysis, such as: daily job risk, work as a disease inducer; work at the laundry and gender; positive feelings towards work; job strain after several years of work; organization of the work; undervaluation of the laundry worker; and suggestions to improve working conditions at the laundry. Conclusion: Based on the results found, we conclude that several workplace environments at the laundry might contribute for the occurrence of noise-induced hearing loss, justifying the investment in hearing conservation programs, particularly aimed to control noise emissions at the source and to intervene in the developing cases of hearing loss caused by noise exposure.